PERBEDAAN KEJADIAN PERTUMBUHAN JANIN TERHAMBAT BERDASARKAN SKOR LUBCHENCO DAN INDEKS PONDERAL PADA BAYI BARU LAHIR DENGAN PREEKLAMPSIA BERAT EARLY DAN LATE ONSET DI RSUD DR SOETOMO SURABAYA - Alvin Saputra, NIM011311133164 (2017)
Background: Maternal Mortality Rate in Indonesia was 359/100.000 live births, while the MDG's was 102/100.000 live births. Under-five years infant mortality rate in Indonesia was 40/1.000 live births, while the MDG's was 32/100.000 live births. The most common causes of maternal deaths in East Java and Surabaya was pre-eclampsia and for infant deaths in Indonesia was low birth weight / prematurity. Pre-eclampsia was a clinical syndrome defined as the new onset of hypertension and proteinuria during the second half period of pregnancy and it can be the risk factor of Intrauterine Growth Restriction (IUGR). Method: This research used retrospective study which use secondary data collected from the medical records with total sampling methods. All of the severe preeclampsia pregnant woman that gave birth in Dr. Soetomo General Hospital Surabaya around January-June 2014. Results: This research there were 69 pregnant women with severe pre-eclampsia, 25 were early and 44 were late onset. From the newborn baby, there were 18 IUGR’s baby. From the analysis of the data by using Chi-square test, obtained p=0.249, so there was no statistically significant difference between the IUGR cases with the type of severe pre-eclampsia. Then the data analysis with samples of newborn baby with IUGR, obtained p=0.197, so there was no statistically significant difference between the type of IUGR with the type of severe preeclampsia. Conclusion: There was not a difference between the IUGR cases with the type of severe preeclampsia according to previous theories.